ABILITY TO TELL STORIES IN BUGIS LANGUAGE FOR CLASS V STUDENTS OF SDN 2 LEJANG, PANGKEP REGENCY - Andi Fatimah Yunus; Nur Zhapira Azzahra; Hajrah (Media Inovasi Pendidikan dan Publikasi, 2024)
This research is a quantitative descriptive study which aims to describe the ability to tell stories in the Bugis language. The population of this research is all class V students of UPT SDN 2 Lejang, Pangkep Regency, 2023/2024 academic year, totaling 50 students. Sampling in this research was carried out using total sampling because the population was less than one hundred. The data collection techniques used in this research were oral test techniques and recording techniques. The data obtained was analyzed using quantitative descriptive analysis. There are four aspects of assessment used in this research, namely the fluency aspect, the use of intonation aspect, the pronunciation aspect, and the voice volume aspect. Based on the analysis of data obtained from the recapitulation of overall scores, the results show that the ability to tell stories in Bugis language of class V students at SDN 2 Lejang, Pangkep Regency is categorized as unable to be proven from the recapitulation of scores table, even though class V students at SDN 2 Lejang obtained an average score of 78 which is at The score range is above 75 and is in the capable criteria, however the percentage of students who get a score above 75 only reaches 68% and does not reach the specified assessment criteria.